FAKTOR YANG BERHUBUNGAN DENGAN PELAKSANAAN KESELAMATAN DAN KESEHATAN KERJA DI RUMAH SAKIT UMUM, KOTA DENPASAR - Dwiari, Kadek Eni; Muliawan, Partha (ARCHIVE OF COMMUNITY HEALTH; Vol 7 No 2 (2020): Desember 2020DO - 10.24843/ACH.2020.v07.i02.p04, 2020)
ABSTRACT Hospital is a service industry with various potential hazards which can cause an accident due to work and illness due to work for the health workers. Therefore, efforts are needed to minimize the risk of harm in the hospital with the implementation of hospital occupational health and safety. This study was a analytical study with a cross-sectional design to know factors related to hospital occupational health and safety implementation. The study was conducted at a public hospital in Denpasar city during March 2019. Number of samples in this study involved 187 among 275 health workers chosen by proportionate stratified random sampling. Data were collected by conducting interviews using a questionnaire. The results showed that 53,48% of health workers have a good implementation of hospital occupational health and safety. The result of chi-square test found that sex, attitude, policy, leadership and the availability of hospital occupational health and safety facilities were the factors related to health workers’ implementation of hospital occupational health and safety (p<0,05). A multivariable analysis showed that attitude was the most significant factor related to health workers’ implementation of hospital occupational health and safety (adjusted PR=1,59; 95% CI 1,11-2,30).